Chelation of mitochondrial iron as an antiparasitic strategy - Arbon, Dominik; Mach, Jan; Čadková, Aneta; Sipkova, Anna; Stursa, Jan; Klanicová, Kristýna; Machado, Marta; Ganter, Markus; Levytska, Viktoriya; Sojka, Daniel; Truksa, Jaroslav; Werner, Lukáš; et al. (ACS infectious diseases, 2024)
Iron, as an essential micronutrient, plays a crucial role in host-pathogen interactions. In order to limit the growth of the pathogen, a common strategy of innate immunity includes withdrawing available iron to interfere with the cellular processes of the microorganism. Against that, unicellular parasites have developed powerful strategies to scavenge iron, despite the effort of the host. Iron-sequestering compounds, such as the approved and potent chelator deferoxamine (DFO), are considered a viable option for therapeutic intervention. Since iron is heavily utilized in the mitochondrion, targeting iron chelators in this organelle could constitute an effective therapeutic strategy. This work presents mitochondrially targeted DFO, mitoDFO, as a candidate against a range of unicellular parasites with promising in vitro efficiency. Intracellular Leishmania infection can be cleared by this compound, and experimentation with Trypanosoma brucei 427 elucidates its possible mode of action. The compound not only affects iron homeostasis but also alters the physiochemical properties of the inner mitochondrial membrane, resulting in a loss of function. Furthermore, investigating the virulence factors of pathogenic yeasts confirms that mitoDFO is a viable candidate for therapeutic intervention against a wide spectrum of microbe-associated diseases.
Gesehen am 03.09.2024